2016
DOI: 10.1016/j.cbi.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of epigenetic inhibitors used for the treatment of cancer

Abstract: This study determined the anti-neoplastic activity and nephrotoxicity of epigenetic inhibitors in vitro. The therapeutic efficacy of epigenetic inhibitors was determined in human prostate cancer cells (PC-3 and LNCaP) using the DNA methyltransferase inhibitor 5-azacytidine (5-Aza) and the histone deacetylase inhibitor trichostatin A (TSA). Cells were also treated with carbamazepine (CBZ), an anti-convulsant with histone deacetylase inhibitor-like properties. 5-Aza, TSA or CBZ alone did not decrease MTT stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…This hypothesis is supported by our previous studies showing that treatment of HEK293 and NRK cells with the HDAC inhibitor TSA upregulated p21 protein expression (Scholpa et al, 2014). We also demonstrated that TSA-induced p21 expression correlated with the increased acetylation of lysine 9 and 14 on histone H3 (H3K9/14 Ac) in the p21 promoter region (Scholpa et al, 2016). However, we do not know the effect of short-and long-term exposure of BrO 3 À on these cells, nor do we know the persistence of these changes.…”
Section: Effect Of Bro 3 2 On P21 Promoter Histone Acetylationsupporting
confidence: 85%
See 3 more Smart Citations
“…This hypothesis is supported by our previous studies showing that treatment of HEK293 and NRK cells with the HDAC inhibitor TSA upregulated p21 protein expression (Scholpa et al, 2014). We also demonstrated that TSA-induced p21 expression correlated with the increased acetylation of lysine 9 and 14 on histone H3 (H3K9/14 Ac) in the p21 promoter region (Scholpa et al, 2016). However, we do not know the effect of short-and long-term exposure of BrO 3 À on these cells, nor do we know the persistence of these changes.…”
Section: Effect Of Bro 3 2 On P21 Promoter Histone Acetylationsupporting
confidence: 85%
“…The first set of samples was collected from passage 1 (P1) of the subchronic regimen, which was continued for 18 days (P6), ie, the cells were treated for 18 days and passaged every 3 days for sample collection. The rationale for this regimen is explained in our previous studies (Scholpa et al, 2014(Scholpa et al, , 2016Zhang et al, 2010Zhang et al, , 2011. In short, we designed a sub-chronic in vitro regimen to obtain the environmentally relevant concentrations and exposures of bromate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive results with 5-Aza suggest that the SIE-1 is an important region for epigenetic regulation of p21 expression. This assertion is strengthened by the fact that we have already shown that 5-Aza alone induced p21 protein expression in these cells 43 . To our knowledge this is the first report demonstrating the methylation of specific DNA bases within p21 promoter that are altered by 5-Aza exposure.…”
Section: Differential Methylation Analysismentioning
confidence: 79%